2016
DOI: 10.1902/jop.2015.150583
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Periodontitis on Adiponectin, C‐Reactive Protein, and Immunoglobulin G Against Porphyromonas gingivalis in Thai People With Overweight or Obese Status

Abstract: Periodontitis and overweight or obese BMI change plasma levels of the inflammatory mediators adiponectin and CRP, independently. This study suggests a role of periodontitis in systemic inflammatory response in Thai people who are overweight or obese.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 44 publications
2
17
0
Order By: Relevance
“…Both obesity and periodontitis can stimulate the up‐regulation of several inflammation factors, such as TNF‐α, IL‐6, and CRP . Periodontitis is a chronic low‐grade inflammatory disease caused by periodontal destructions over time .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both obesity and periodontitis can stimulate the up‐regulation of several inflammation factors, such as TNF‐α, IL‐6, and CRP . Periodontitis is a chronic low‐grade inflammatory disease caused by periodontal destructions over time .…”
Section: Discussionmentioning
confidence: 99%
“…Both obesity and periodontitis can stimulate the upregulation of several inflammation factors, such as TNF-, IL-6, and CRP. 27 Periodontitis is a chronic low-grade inflammatory disease caused by periodontal destructions over time. 11 In this study, periodontal attachment level and HE staining of teeth showed that experimental periodontitis caused significant attachment loss and alveolar bone destruction.…”
Section: Discussionmentioning
confidence: 99%
“…A systemic proinflammatory state in obesity is suggested for increased alveolar bone loss with altered immune response because of compromised functional state of immune cells . C‐reactive protein (CRP) in particular, is a marker of systemic inflammation and is associated with obesity and periodontitis . Elevated levels of CRP is characterized by dysregulated and increased production of several proinflammatory cytokines that are implicated in the pathogenesis of periodontal destruction …”
Section: Introductionmentioning
confidence: 99%
“…9 C-reactive protein (CRP) in particular, is a marker of systemic inflammation and is associated with obesity and periodontitis. 10 Elevated levels of CRP is characterized by dysregulated and increased production of several proinflammatory cytokines that are implicated in the pathogenesis of periodontal destruction. 9,11,12 In the past decade, obesity has been thoroughly investigated as one of the risk factors for periodontal tissue destruction and association between increased adiposity and poor periodontal outcomes is well elucidated; [13][14][15][16] In a recent cross-sectional study by Abduljabbar and colleagues, 17 it was concluded that obese individuals showed increased peri-implant probing depth (PD) and higher amount of marginal bone loss (MBL) as compared to nonobese individuals.…”
mentioning
confidence: 99%
“…Poor oral health promotes obesity, obesity impacts on oral inflammation, or the relationship may be a combination of both mechanisms. The increased serum inflammatory markers from both diseases suggest that systemic inflammation plays a key role in the process (Pischon et al., ; Thanakun & Izumi, ).…”
Section: Introductionmentioning
confidence: 99%